The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1097/inf.0000000000001864
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pharyngitis Associated With Streptococcus dysgalactiae Subspecies equisimilis in Children

Abstract: Background and Objectives: The importance of Streptococcus dysgalactiae subsp. equisimilis (SDSE) in causing sporadic pharyngitis in children remains controversial. The aims of this study were (1) to report the incidence and (2) to compare the epidemiologic and clinical features of patients with SDSE to those with Streptococcus pyogenes (SP). Methods: A prospective study was conducted on acute pharyngitis associated with SDSE in children over a 2-year p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The patient in this report started with an upper respiratory tract infection that led to the lethal form of toxic shock syndrome in a few days. In a recent study, SDSE has been identified in 2% of cases of acute pharyngitis, predominantly in schoolchildren 20 , apparently with a favorable course.…”
Section: Discussionmentioning
confidence: 95%
“…The patient in this report started with an upper respiratory tract infection that led to the lethal form of toxic shock syndrome in a few days. In a recent study, SDSE has been identified in 2% of cases of acute pharyngitis, predominantly in schoolchildren 20 , apparently with a favorable course.…”
Section: Discussionmentioning
confidence: 95%
“…Treatment recommendations for SDSE infections are widely described in the literature and are based on multiple strains [123,152]. Kakuya et al [152] based their recommendations on the study of more than 3000 isolates isolated from pharyngitis. Extensive use of cephalosporins is suggested in cases of throat infections.…”
Section: Streptococcus Dysgalactiae Subsp Equisimilis (Sdse)mentioning
confidence: 99%
“…Treatment recommendations for SDSE infections are widely described in the literature and are based on multiple strains [123, 152]. Kakuya et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deterioration of infection may also lead to systemic complications such as acute nephritis, sepsis, rheumatic fever, and other diseases [3][4][5]. The incidence of pharyngitis has reached 20%-50% according to the epidemiological statistics [6,7]. Pharyngitis is a common upper respiratory tract disease in adults with long course of disease and stubborn symptom which are difficult to cure.…”
Section: Introductionmentioning
confidence: 99%